2007
DOI: 10.1197/jamia.m2292
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based Insulin Infusion Protocol Improves Glycemia Control over Manual Protocol

Abstract: The CPOE-based intravenous insulin protocol improved glycemia control in SICU patients compared to a previous manual protocol, and reduced time to insulin therapy initiation. Integrating a computer-based insulin protocol into a CPOE system achieved efficient, safe, and effective glycemia control in SICU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 33 publications
1
112
1
Order By: Relevance
“…Recently, a computer‐based insulin infusion protocol has been introduced in the ICU setting, for which improved glycemic control over the manual protocol was reported 38. Saur et al 39.…”
Section: Insulin Therapy In Patients With Perioperative Hyperglycemiamentioning
confidence: 99%
“…Recently, a computer‐based insulin infusion protocol has been introduced in the ICU setting, for which improved glycemic control over the manual protocol was reported 38. Saur et al 39.…”
Section: Insulin Therapy In Patients With Perioperative Hyperglycemiamentioning
confidence: 99%
“…[16][17][18] Though intravenous insulin use was associated with better overall glucose control in our study; only about 50% of ICU patients received it on measurement day 1. A recent prospective randomized clinical trial demonstrated superior glycemic control in non-critically ill hospitalized patients with type 2 diabetes with basal/bolus insulin therapy compared to sliding scale insulin alone.…”
Section: Discussionmentioning
confidence: 53%
“…15 There is now emerging consensus that use of continuous insulin infusion given through a standardized protocol is the standard of care to control hyperglycemia in critically ill patients. [16][17][18] Likewise, use of specific hospital insulin regimens that include basal and short-acting insulin with appropriate bedside glucose monitoring and avoiding use of ''sliding scale'' short-acting insulin alone has become recognized as the most effective approach for glucose management in hospitalized patients not requiring intravenous insulin. 4,[19][20][21] The University HealthSystem Consortium (UHC) is an alliance of 97 academic health centers and 153 of their associated hospitals that conducts benchmarking studies on clinical and operational topics with member academic medical centers and develops new programs to improve quality of care, patient safety, and operational, clinical, and financial performance.…”
mentioning
confidence: 99%
“…136 It is advisable to keep glycemia between 140 and 180 mg/dL. 137 Nutrition support should be considered in septic patients and enteral nutrition should be preferred to parenteral one. At the moment, there is not enough evidence to recommend more precise advice regarding doses and timing.…”
Section: Other Measuresmentioning
confidence: 99%